Lola Apk in Junior High School Speaking Class: Students’ Point of View - Hamdany, Syahwan; Rahman, Benni Ichsanda (Institut Agama Islam Negeri Palopo, 2025)
This study intends to examine how junior high school students see the use of the Lola Speak application to enhance their English speaking abilities. Students' subjective experiences were investigated using a qualitative approach and a case study methodology. Semi-structured interviews and questionnaires were used to gather information from 24 first-graders at a Medan junior high school. Ten closed-ended statements that assessed the application's usefulness, simplicity of use, and effect on students' confidence in their ability to speak English made up the questionnaire. The majority of pupils gave the application positive feedback, according to the data. Up to 66.7% of students concurred that the application's speaking practice feature enhanced their ability to communicate, and 58.3% said that using it increased their confidence when speaking English. The application was also thought to be engaging, user-friendly, and capable of boosting motivation for learning. Some students, however, claimed that in order to better accommodate different learning styles, more features were required and that there were technical limitations. The study's findings emphasize how critical it is to create application-based learning tools that are more flexible and sensitive to user requirements.